Impact of Semantic Cueing of Verb and Its Thematic Role on Discourse Skills of Persons with Aphasia - Puttanna, Deepak; Puri, Goswami Sathyapal; Swamy, Akshaya (Journal of Health and Allied Sciences NU, 2024)
Introduction Understanding the relationship between word retrieval treatment and discourse skills is deemed pivotal, as it gives the individuals a more naturalistic linguistic performance.Objective The aim of this study was to unravel the impact of word retrieval treatment on discourse skills.Method and Materials Semantic cueing of verbs and its thematic role (SCVTr) treatment were rendered to 11 persons with aphasia (PWAs). Subsequent to therapy, discourse skills were evaluated in the pretreatment, midtreatment, posttreatment, and follow-up phases using both qualitative (discourse analysis scale) and quantitative (T-unit analysis) measures. The follow-up phase in the study began after 1 month of cessation of treatment.Results The outcome of the study evinced statistical differences in the discourse skills in both qualitative and quantitative measures of discourse between pre-, mid-, and posttreatment phases. However, no statistical difference was found between the posttreatment and follow-up phases across qualitative and quantitative measures. This signifies there are no differences in discourse skills after the cessation of treatment.Conclusion The study findings seemed to be novel, as the study explored the impact of word retrieval treatment on discourse skills. It also sheds light on the importance of discourse analysis and the ways of measuring it in PWAs. Overall, the study finding seems conducive as it posits positive outcomes in both qualitative and quantitative measures of discourse skills following word retrieval treatment.
Keywords: word retrieval; discourse; semantic treatment; anomia